Subjective mechanisms for survival in the unfamiliar schooling space: Special needs teachers’ lived experiences - Rinquest, E. (South African Journal of Higher Education, 2024)
The research discussed in this article explores the experiences of special needs educators teaching the Curriculum and Assessment Policy Statement (CAPS) to diverse learners in a Cape Town special school. This study delves into how six teachers positioned themselves within the school’s discourses and culture, employing an interpretive approach and drawing on theoretical frameworks such as Lefebvre’s theory of spatial production, Bourdieu’s concept of habitus, and Nespor’s ideas related to bodies in space. The results highlighted the impact of the school’s institutional culture, influenced by class, race, and age, on the teachers’ personal and professional socialisation experiences. The research for this article focused on the real-life encounters of special needs educators handling diverse students in a Cape Town school, while implementing the CAPS curriculum. The study investigated how six teachers positioned themselves in relation to the prevailing discourses and culture of the school by taking an interpretivist approach and drawing on Lefebvre’s theory of the creation of space, Bourdieu’s (1977) idea of habitus, and Nespor’s (1997) theory regarding bodies in space. The results showed that the institutional culture of the school, which was moulded by concerns of class, colour, and age, had a substantial impact on the socialisation processes of the teachers on a personal and professional level. These teachers were able to reposition themselves in relation to the institutional culture and to establish their professional identities based on their individualised ways of acting and living in the school. The study’s conclusions have consequences for teacher education and policy development, highlighting the necessity of viewing these instructors as a result of the uneven South African educational system rather than as a homogenous group.